Propionibacterium acnes: A Treatable Cause of Constrictive Pericarditis - Daniel Cruz; Haitham Ahmed; Yousuf Gandapur; M. Roselle Abraham (Case Reports in Medicine)
In this case report we share a case of infective Pericarditis caused by Propionibacterium acnes (P. acnes) in an immune-competent, nonsurgical patient. This case and review will illustrate the importance of considering P. acnes as a cause of idiopathic pericardial effusion and effusive constrictive disease. The patient was a 61-year-old male with history of osteoarthritis of the knee. He received an intra-articular steroid injection in July 2013. Two months later, he presented with atrial fibrillation and heart failure. He was found to have pericardial and bilateral pleural effusions which grew P. acnes. This organism was initially considered to be contaminant; however, as P. acnes was isolated from both pleural and pericardial fluids, he was started on oral amoxicillin. He was noted to have recurrence of effusions within 2 weeks with evidence of constrictive physiology by echocardiography. Treatment was subsequently changed to intravenous Penicillin G with marked symptomatic improvement, resolution of pericardial/pleural effusions, and no echocardiographic evidence of constrictive pericarditis at 10 weeks follow-up. Pursuit and treatment of P. acnes could lead to prevention of constrictive pericarditis. We believe that further studies are needed to assess prevalence of P. acnes and response to intravenous Penicillin G in patients presenting with effusive constrictive disease.